2014
DOI: 10.1186/s40001-014-0058-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of radical nephrectomy versus nephron-sparing surgery on localized renal cell carcinoma

Abstract: BackgroundThe aim of the present study was to compare the clinical efficacy of radical nephrectomy (RN) with nephron-sparing surgery (NSS) in treating patients with localized renal cell carcinoma (RCC).MethodsThe literature search was performed in PubMed, MEDLINE Springer, Elsevier Science Direct, Cochrane Library, and Google Scholar up to December 2012. The software Review Manager 5.1 and the STATA software package v.11.0 were used for analyses. The odds ratios (ORs) and its 95% confidence interval (95% CI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…[7] In the literature, many studies have investigated the incidence of renal malignancies in various age groups. [1][2][3][4][5][6] In a large series Open partial nephrectomy, n (%) 4 (14) 21 (21) Laparoscopic radical nephrectomy, n (%) 2 (7) 11 (11) Fuhrman grading system (for only malignancies), n (%) consisting of 2710 cases, RCC was reported in 2164 cases; 4% of which comprised of patients aged between 20 and 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…[7] In the literature, many studies have investigated the incidence of renal malignancies in various age groups. [1][2][3][4][5][6] In a large series Open partial nephrectomy, n (%) 4 (14) 21 (21) Laparoscopic radical nephrectomy, n (%) 2 (7) 11 (11) Fuhrman grading system (for only malignancies), n (%) consisting of 2710 cases, RCC was reported in 2164 cases; 4% of which comprised of patients aged between 20 and 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a large number of meta analyses regarding the comparison of radical nephrectomy (RN) and PN have been reported (7, 8), but few are about the comparison of TE and PN. Minervini et al (9) performed a meta-analysis comparing several oncologic outcomes following TE and PN for renal cell carcinoma, and demonstrated that TE was at least non-inferior to PN.…”
Section: Introductionmentioning
confidence: 99%
“…Although local recurrence rate is potentially higher in the partial nephrectomy group ( Fig. 16.4a, b ), a recent meta-analysis has shown that NSS had a signifi cantly lower cancer-specifi c death rate compared with RN, but there was no signifi cant difference in the rate of tumour recurrence and complications between the two techniques [ 20 ].…”
Section: Open Partial Nephrectomy (Pn) or Nephron-sparing Surgery (Nss)mentioning
confidence: 96%